"We come as friends": approaches to social accountability by health committees in Northern Malawi - Elsbet Lodenstein; Joyce M. Molenaar; Christine Ingemann; Kondwani Botha; Jenipher Jere Mkandawire; Loan Liem; Jacqueline E. W. Broerse; Marjolein Dieleman (BMC, 2019)
Abstract Background In Malawi, as in many low-and middle-income countries, health facility committees (HFCs) are involved in the governance of health services. Little is known about the approaches they use and the challenges they face. This study explores how HFCs monitor the quality of health services and how they demand accountability of health workers for their performance. Methods Documentary analysis and key informant interviews (7) were complemented by interviews with purposefully selected HFC members (22) and health workers (40) regarding their experiences with HFCs. Data analysis was guided by a coding scheme informed by social accountability concepts complemented by inductive analysis to identify participants' perceptions and meanings of processes of social accountability facilitated by HFCs. Results The results suggest that HFCs address poor health worker performance (such as absenteeism, poor treatments and informal payments), and report severe misconduct to health authorities. The informal and constructive approach that most HFCs use is shaped by formal definitions and common expectations of the role of HFCs in service delivery as well as resource constraints. The primary function of social accountability through HFCs appears to be co-production: the management of social relations around the health facility and the promotion of a minimum level of access and quality of services. Conclusions Policymakers and HFC support programs should take into account the broad task description of HFCs and integrate social accountability approaches in existing quality of care programs. The study also underscores the need to clarify accountability arrangements and linkages with upward accountability approaches in the system.